Pharmacokinetic Aspects of Nanoparticle-in-Matrix Drug Delivery Systems for Oral/Buccal Delivery - Feitosa, Renata Carvalho; Geraldes, Danilo Costa; Beraldo-de-Araújo, Viviane Lucia; Costa, Juliana Souza Ribeiro; Oliveira-Nascimento, Laura (Frontiers in Pharmacology, 2019)
Oral route maintains its predominance among the ones used for drug delivery, especially when medicines are self-administered. If the dosage form is solid, therapy gains in dose precision and drug stability. Yet, some active pharmaceutical substances do not present the required solubility, permeability or release profile for incorporation into traditional matrices. The combination of nanostructured drugs (NP) with these matrices is a new and little-explored alternative, which could bring several benefits. Therefore, this review focused on combined delivery systems based on nanostructures to administer drugs by the oral cavity, intended for buccal, sublingual, gastric or intestinal absorption. We analyzed published NP-in-matrix systems and compared main formulation characteristics, pharmacokinetics, release profiles and physicochemical stability improvements. The reported formulations are mainly semisolid or solid polymers, with polymeric or lipid nanoparticles and one active pharmaceutical ingredient. Regarding drug specifics, most of them are poorly permeable or greatly metabolized. The few studies with pharmacokinetics showed increased drug bioavailability and, sometimes, a controlled release rate. From our knowledge, the gathered data make up the first focused review of these trendy systems, which we believe will help to gain scientific deepness and future advancements in the field.